1998
DOI: 10.1590/s0074-02761998000300003
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Campylobacter Isolates from Three Activated Sludge Systems

Abstract: Thermophilic campylobacters were isolated from three sewage plants in Rio de Janeiro, RJ, Brazil and identified

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…1988; Stampi et al. 1992; Lauria‐Filgueiras and Hofer 1998). In the UK, reductions of between 86% and 99% were obtained for a large WWTW at Salford (Greater Manchester), of between 79% and 99% for a rotary biofilm treatment system at Middleton (Morecambe) and of between 95% and 100% for a small WWTW at Caton.…”
Section: Campylobacters In Sewagementioning
confidence: 99%
See 2 more Smart Citations
“…1988; Stampi et al. 1992; Lauria‐Filgueiras and Hofer 1998). In the UK, reductions of between 86% and 99% were obtained for a large WWTW at Salford (Greater Manchester), of between 79% and 99% for a rotary biofilm treatment system at Middleton (Morecambe) and of between 95% and 100% for a small WWTW at Caton.…”
Section: Campylobacters In Sewagementioning
confidence: 99%
“…Results from several continents have shown that campylobacters are ubiquitous in sewage and that humans and animal waste from abattoirs and animal treatment plants are the major sources (Arimi et al 1988;Ho Èller 1988;Stelzer et al 1988Stelzer et al , 1991Jones et al 1990a, b;Betaieb and Jones 1990 7 ; Stampi et al 1992;Koenraad et al 1994;Lauria-Filgueiras and Hofer 1998;Stampi et al 1999). Analysis of individual sewers in Lancaster, UK, showed that Campylobacter numbers were related to the incidence of campylobacteriosis in subdivisions of the city and to the presence of animal ef¯uent from abattoirs and poultry processing ).…”
Section: Campylobacters In Sewagementioning
confidence: 99%
See 1 more Smart Citation
“…Collected samples were maintained at 10ºC of refrigeration, from 2 h to four days until laboratorial processing. Feces were sent to the Bacterial Zoonosis Laboratory of the Department of Bacteriology, Fiocruz, Rio de Janeiro, Brazil, where they were tested according to a previously commended protocol (Lauria-Filgueiras & Hofer 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Considerable reduction of Campylobacter in sewage can be achieved by secondary treatment (i.e. trickle filtration, activated sludge and oxidation ponds) where the numbers of campylobacters could be reduced by 88% to over 95% [46,49]. Complete elimination of campylobacters from sewage effluents can be achieved by tertiary treatment and chlorination [50].…”
Section: Sewage Effluents and Sludgementioning
confidence: 99%